Association between coping strategies and drug use in a large cohort of students from a northern Italian University. - Caricati, Luca; Ferrari, Davide (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Illicit drug (ID) use/abuse represent a social and economic burden for most countries worldwide which, in spite of the efforts to prevent this phenomena, is often a growing habit especially in the young adults. Preventive measurements, are needed to reduce the adverse health and social consequences of ID use/abuse. Methods. This study investigated the relationship between coping strategies and ID use in students (N=12316) from the University of Parma, Italy. Information about the ID use in the past 12 months and coping strategies were collected with a cross-sectional research design using an online questionnaire. Results. More than 25% of the participants used ID in the past year; men were more likely to use drugs than female; the likelihood of using drugs was inversely related to age. The relationship between coping strategies and ID use was analyzed with a multilevel logistic model taking into account the within-department nested structure of data. Analysis revealed that transcendence-orientation and problem-orientation were associated with a reduction of the likelihood to have used drugs. Conversely, avoidance and positive attitude were associated with an increase of the likelihood to have used drugs. Finally, seeking social support revealed a positive but modest association with increasing in drug use. Conclusions. The ID use association factors identified in this study could be utilized by the appropriate institutions/authorities as a critical review in order to develop relevant public health policies and preventive measures aimed at minimizing the use of ID in this critical age group.